Effect of the external magnetic field on the dynamics and power of the self-sustained plasma-beam discharge - Hrechko, Ya.O.; Azarenkov, N.A.; Babenko, Ie.V.; Ryabchikov, D.L.; Sereda, I.N.; Boloto, D.A.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2018)
The paper is related to the studying the effect of the external constant magnetic field on the dynamics and power of the self-sustained plasma-beam discharge. It is shown that a relatively small (up to 1 kG) magnetic field of a specific configuration allows to increase the power inputted into the discharge at several times. The distinctive features of the discharge in the presence of the external constant magnetic field are noted.